Content Analysis and Implementation of Biology Online Learning Materials in SMA/MA/SMK During The COVID-19 Pandemic - Ferdyan, Rhavy; Lufri, Lufri; Zulyusri, Zulyusri (Journal of Biology Education, 2020)
This article aims to explain the content and implementation of online biology learning materials during the COVID-19 pandemic in SMA / MA / SMK. Face-to-face learning that is transformed into online learning has a profound impact on the content and amount of material taught by teachers to students. Even with the implementation of the emergency curriculum which reduces some basic competencies in one subject, there are still materials that are not conveyed by the teacher for several reasons. This is due to the selection of essential materials, allocation of time, facilities and media, as well as student learning fatigue using online platforms.